Implementation of Change Management in the Human Resources Management Process - Budi Rismayadi (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2024)
This research aims to investigate the implementation of change management in the context of human resource management (HR). Change management is becoming increasingly important in the face of rapidly changing organizational dynamics and business environments. However, how change management is implemented effectively in the HR management process is still an important research subject. This research will use a qualitative approach with descriptive methods. The research results show that the impact of globalization on human resource management (HR) creates various new challenges for companies. Intense global competition, shortage of skilled labor, cultural diversity, high labor mobility, and technological changes are the main factors influencing HR strategies in the era of globalization. To overcome these challenges, companies need to adopt effective change management strategies. These strategies include good communication, employee participation, training and development, forming effective work teams, and recognizing employee contributions. By implementing a holistic approach in HR change management, companies can optimize their performance amidst ever-changing global business dynamics, and create an inclusive, innovative and highly competitive work environment.